2018
DOI: 10.1016/j.brat.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in working memory is associated with fear extinction performance

Abstract: PTSD has been associated consistently with abnormalities in fear acquisition and extinction learning and retention. Fear acquisition refers to learning to discriminate between threat and safety cues. Extinction learning reflects the formation of a new inhibitory-memory that competes with a previously learned threat-related memory. Adjudicating the competition between threat memory and the new inhibitory memory during extinction may rely, in part, on cognitive processes such as working memory (WM). Despite sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…4a,b). This evidence is in line with the idea that, rather playing a role in the acquisition of conditioning 29 , individual differences in working memory may become crucial for the recall and strategic use of past learning. However, since the present experiment was not specifically designed to address this hypothesis, conclusion on this issue should be cautious 32 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4a,b). This evidence is in line with the idea that, rather playing a role in the acquisition of conditioning 29 , individual differences in working memory may become crucial for the recall and strategic use of past learning. However, since the present experiment was not specifically designed to address this hypothesis, conclusion on this issue should be cautious 32 .…”
Section: Discussionsupporting
confidence: 88%
“…When facing multiple R− > O (instrumental learning) and S− > O (Pavlovian learning) associations, individual differences in working memory may, thus, influence the accessibility of such representations to control subsequent behavioral expressions 28 . Interestingly, recent findings suggest that high working memory capacity is not associated with the expression of conditioning per se (i.e., learning of the contingencies), but rather with a more effective use of the acquired information in later phases 29 . In particular, as compared to general PIT, outcome-specific PIT requires retaining a detailed representation of the outcomes available and of each response-outcome pairing 30 , thus it should rely more on working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is important to mind the influence cognitive load has on affective processing in relation to differential aversive conditioning processes (Raes et al, 2009;Stout et al, 2018;Laing et al, 2019;de Voogd and Phelps, 2020). Specifically, previous reports have indicated working memory load moderates the association between anxiety and differential aversive conditioning acquisition (Laing et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, much of this work has found that anxious individuals demonstrated enhanced conditioning acquisition (Lissek et al, 2005) and impaired extinction (Barrett and Armony, 2009;Duits et al, 2015), or the ability to learn that a CS+ no longer is associated with an aversive outcome after several presentations of the CS+ without an aversive outcome. While this body of work is important, less remains known regarding how these threat-conditioned stimuli influence higher order cognitive systems, especially given that previous reports have found evidence indicating that these systems alter aversive conditioning processes (Raes et al, 2009;Fani et al, 2012;Stout et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with deficits in executive functioning might benefit from cognitive support strategies that help them attend to or remember the contents of the session (e.g., by reducing the length of the session or increasing session frequency), whereas patients with less activity in areas related to emotional biases might benefit from strategies that benefit from the reactivation of (emotional) memory structures or activation of a sufficient amount of emotional arousal that is necessary for changing, activating, or deactivating memory. In line with this suggestion, a recent study pointed to the importance of individual differences by showing that participants with better working memory showed better fear extinction compared with those with worse working memory (Stout et al, 2018). It might also be beneficial for CBT to distinguish between individual differences in memory structure(s) that maintain the depression by measuring the idiosyncratic dysfunctional beliefs of the patient and adapting CBT procedures to this specific memory.…”
Section: Directions For Future Research To Improve Cbtmentioning
confidence: 96%